Kinetics of Isothermal Degradation Studies in Adhesives by Thermogra vimetric Data: Effect of Hydrophilic Nanosilica Fillers on the Thermal Properties of Thermoplastic Polyurethane-Silica Nanocomposites - Jose-Roberto, Vega-Baudrit (2008)
The kinetics of thermal degradation process on thermoplastic polyurethanes (TPUs) adhesives with hydrophilic nanosilicas was studied using isothermal thermogravimetric analysis within the temperature range from 360 °C to 460 °C in nitrogen. The effect of nanosilicas with different hydrophilic degree in the thermoplastic polyurethanes was investigated. It was found that the thermoxidative degradation of polyurethane-silica nanocomposites takes place in one step. An analysis of the isothermal methods to evaluate kinetic parameters of decomposition of solids from isothermal thermogravimetric data is presented. Patents WO07146353A2 and US20070292623A1 have some relevant information about the topic develop in this study, because the principle in both cases relies on the interactions between reactive groups in the polymer (TPUs) and the silanol in the silica nano-particles.